Which role for synthetic ligaments in the reconstruction of patellar tendon chronic rupture after TKA? Mid-term outcomes using LARS ligament. - Giuntoli, Michele; Bonicoli, Enrico; Piolanti, Nicola; Ipponi, Edoardo; Vigorito, Antonella; Marchetti, Stefano; Scaglione, Michelangelo (Acta Biomedica Atenei Parmensis, 2020)
Background and aim of the work: Patellar tendon rupture is a rare complication after Total Knee Arthroplasty (TKA) which often requires surgical treatment. Patients with chronic lesions or tendon degenerations showed good results when treated using autografts or allografts, but these techniques showed poor outcomes at long-term follow-up (FU). Moreover, allografts have high costs and limited availability, not to mention the increased risk of immune reactions and infections. Recently, the use of synthetic ligaments for patellar tendon reconstruction has taken hold with encouraging results. We report our experience in the treatment of patellar tendon ruptures after TKA using the Ligament Advanced Reinforcement System-LARS®.Methods: Clinical evaluation was performed using the Knee Society Score and recording extensor lag. Instrumental evaluation was performed using ultrasound imaging to assess patellar tendon thickness and using conventional x-rays to assess prosthesis’ mobilization signs and patella’s height.Results: At the final FU, 6 knees were included in our study. Patient’s mean age was 66.7. Patellar tendon reconstruction occurred after a mean time of 4 months from the previous surgery. The mean FU was 44,2 months. The mean Knee Score was 63.3 and the mean Function Score was 35. In 4 knees the extensor lag was < 10° while in 2 knees it was > 20°. The mean ISI was 1.16, while the average increment in tendon thickness was 127.12%.Conclusions: In our opinion, synthetic ligaments can be successfully employed for the reconstruction of patellar tendon breakage after TKA and rTKA in selected patients, in order to quickly return them to their activity of daily living.